Marsilio de Padua y Maquiavelo: una lectura comparada - Bayona Aznar, Bernardo (Foro Interno, 2007)
Marsilius of Padua’s thinking represents an unprecedented attempt to base power on rational grounds. Two centuries earlier than Machiavelli, Marsilius had developed a political theory that was very different from traditional medieval thought and had offered for the first time an autonomous explanation of power, without referring to a higher order or law to justify its existence. These two Italian writers were passionate about politics and, touched by the political instability in their motherland, sought to maintain peace. They held that the State does not have a moral purpose, only a political one, and that the prince’s or ruler’s task is to guarantee that it functions, making use of coercion or force as necessary. This article deals with the main commonalities and differences between the two philosophers.